Study guides

☆☆

Q: How do you factor 6a2 plus 5a-4?

Write your answer...

Submit

Still have questions?

Related questions

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)

3a(2a + 1)

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)

5 - a - 1 + c - 6a2 + a2

5a4 + 3a3 + 2a2

2a(3a - 4b + 1)

(3a - 2b)(2a + 3b)

-5a4 The coefficient would be -5. The variable is a and the power is 4.

The GCF of 6a^2 and 8a is 2a.

6a2 - 8ab + 2aas you can see a is common to all terms. And 2 is a factor of 6,8, and 2. So 2a is a factor of all three terms:2a(3a-4b+1)

6a2

18a2 + 16a + 38 = 3(6a2 + 8a + 19)

People also asked